SENTIK: Web module for the systematization of information in social networks analysis - Torres, Bey Jamelyd López; Bautista, Humberto Martínez (AWARI, 2023)
This article aimed to demonstrate the utility and application of the SENTIK web module, designed to assist in the systematization of data obtained through social network analysis. Its operation relies on the use of alphanumeric keys, which ensures the protection of personal data, actor classification, and network visualization and prevents actor duplication. The design was achieved through the integration of languages and add-ons such as HTML, CSS, JavaScript, jQuery, PHP, and MySQL, enabling its execution across various browsers. Its design is multi-platform and freely accessible. The module is original, user-friendly, and intuitive, with its value lying in the reduction of effort and time that social researchers will invest in processing their relational data. Moreover, this tool aims to attract new researchers to address social issues through a network analysis approach.